Pontocerebellar atrophy is the hallmark neuroradiological finding in late-onset Tay-Sachs disease - Májovská, Jitka; Hennig, Anita; Nestrasil, Igor; Schneider, Susanne A; Jahnová, Helena; Vaněčková, Manuela; Magner, Martin; Dušek, Petr (Neurological sciences, 2022)
PURPOSE: Late-onset Tay-Sachs disease (LOTS) is a form of GM2 gangliosidosis, an autosomal recessive neurodegenerative disorder characterized by slowly progressive cerebellar ataxia, lower motor neuron disease, and psychiatric impairment due to mutations in the HEXA gene. The aim of our work was to identify the characteristic brain MRI findings in this presumably underdiagnosed disease. METHODS: Clinical data and MRI findings from 16 patients (10F/6 M) with LOTS from two centers were independently assessed by two readers and compared to 16 age- and sex-related controls. RESULTS: Lower motor neuron disease (94%), psychiatric symptoms-psychosis (31%), cognitive impairment (38%) and depression (25%)-and symptoms of cerebellar impairment including dysarthria (94%), ataxia (81%) and tremor (69%), were the most common clinical features. On MRI, pontocerebellar atrophy was a constant finding. Compared to controls, LOTS patients had smaller mean middle cerebellar peduncle diameter (p < 0.0001), mean superior cerebellar peduncle diameter (p = 0.0002), mesencephalon sagittal area (p = 0.0002), pons sagittal area (p < 0.0001), and larger 4th ventricle transversal diameter (p < 0.0001). Mild corpus callosum thinning (37.5%), mild cortical atrophy (18.8%), and white matter T2 hyperintensities (12.5%) were also present. CONCLUSION: Given the characteristic clinical course and MRI findings of the pontocerebellar atrophy, late-onset Tay-Sachs disease should be considered in the differential diagnosis of adult-onset cerebellar ataxias.
Keywords: Cerebellar atrophy; gangliosidózy GM2; Motor Neuron Disease; HEXA gene; onemocnění motorického neuronu; nemoci mozečku; Late-onset Tay-Sachs disease; nemoci s pozdním začátkem; Tay-Sachsova nemoc; Adult; Cerebellar Diseases; atrofie; Tay-Sachs Disease; GM2 gangliosidosis; magnetická rezonanční tomografie; Magnetic Resonance Imaging; Humans; Late Onset Disorders; dospělí; Gangliosidoses, GM2; Ataxia; lidé; Atrophy